Change Readiness Among UCU Staff With Special Attention to Employee Participation - Grace Nakikonyogo (Uganda Christian University, 2024)
This study aims to explore the strategies to enhance employee change readiness on promoting active participation among employees. The research data was collected from Uganda Christian University, Mukono. This study was guided by three main objectives namely, to assess the perceived level of employee readiness for change among non-teaching staff of Uganda Christian University, to examine the level of employee participation during changes in Uganda Christian University, explore the possible contribution of employee participation in fostering employee change readiness. A qualitative approach was employed to collect data from the representatives of 12 respondents from the teaching staff of UCU. These respondents have been at UCU for five years and above. The data collection was done through semi- structured interviews and was done inductively. The results indicated that openness and embrace to change, adaptability, dedication and commitment, sense of control and confidence were considered to be instrumental that influenced employee readiness to change. Other factors that emerged as important included, support from the management, provision of incentives, open communication, training and employee empowerment. The study can be said to have identified some of the successful factors that can identify the readiness of UCU employees from the results.